2005
DOI: 10.1177/1077558704273769
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Home Profit Status and Quality of Care: Is There Any Evidence of an Association?

Abstract: This article critically reviews the association between the profit status of North American nursing homes and the quality of care. Studies were identified by searching MEDLINE (January 1990-October 2002), reference lists, letters, commentaries, and editorials. The quality indicator(s) used to measure quality of care, and its relationship to profit status, was extracted from each publication. The study design and risk-adjustment methodologies used were also extracted. The interrater reliability for the extracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
179
4
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(200 citation statements)
references
References 57 publications
9
179
4
2
Order By: Relevance
“…Although Hillmer et al (2005) concluded that FP nursing home status was often associated with reduced quality of care across many important indicators, these data do not provide definitive evidence that FP status is associated, either negatively or positively, with quality of home care.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Although Hillmer et al (2005) concluded that FP nursing home status was often associated with reduced quality of care across many important indicators, these data do not provide definitive evidence that FP status is associated, either negatively or positively, with quality of home care.…”
Section: Discussionmentioning
confidence: 43%
“…However, some research has been carried out in the LTC and acute care sectors exploring the relationship between quality of care and staffing levels (Porell & Caro, 1998;Zinn, Aaronson, & Rosko, 1993;Needleman, Buerhaus, Mattke, Stewart, & Zelevinsky, 2002), the size of the organization (Zinn et al, 1993;Porell & Caro, 1998;Teare, Hirdes, Ziraldo, Proctor, & Nenadovic, 2000), for-profit (FP) versus notfor-profit status (NFP) (Hillmer, Wodchis, Gill, Anderson, & Rochon, 2005) and accreditation results (Miller et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a substantial body of published research supporting the measurement of staffing as a recognized "structural" indicator of nursing home quality, 3,4 we were careful in our article to also make this point. We hope that our study will encourage further Canadian research on this question.…”
Section: Ed Helfrichmentioning
confidence: 99%
“…Driven by profit maximizing, for-profit nursing homes have been shown to provide poorer quality compared to non-profit nursing homes [34][35][36][37].…”
Section: Evidence Of Low Quality In Nursing Homes and Changes In Qualmentioning
confidence: 99%